2007
DOI: 10.3310/hta11530
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the impact of the NHS Health Technology Assessment Programme

Abstract: It produces high-quality research information on the costs, effectiveness and broader impact of health technologies for those who use, manage and provide care in the NHS. 'Health technologies' are broadly defined to include all interventions used to promote health, prevent and treat disease, and improve rehabilitation and long-term care, rather than settings of care. The research findings from the HTA Programme directly influence decision-making bodies such as the National Institute for Health and Clinical Exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
162
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(174 citation statements)
references
References 34 publications
(61 reference statements)
7
162
0
5
Order By: Relevance
“…In addition to being fully acknowledged, this danger was mitigated by being supervised by an independent Advisory Group (8). Neither the HTA Program nor NCCHTA had any influence on the conduct of the research or its interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being fully acknowledged, this danger was mitigated by being supervised by an independent Advisory Group (8). Neither the HTA Program nor NCCHTA had any influence on the conduct of the research or its interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of studies of the impact from health research programs was linked to the work reported here (8). Several studies examined the payback from diverse research programs (as opposed to individual projects), generally indicating a higher level of impact than is often thought to exist.…”
mentioning
confidence: 99%
“…[33][34][35][36] We assumed, however, that we should interpret our research question to focus on whether or not any identified improvements in the performance of clinicians or health-care organisations had resulted in some way from the processes of their being engaged in research, whether or not that improvement occurred concurrently with the conduct of research or subsequently. In our search for papers it proved challenging to establish the precise inclusion criteria to enable us to focus on this interpretation, and we return to this issue at several points in this report.…”
Section: Scope Of the Reviewmentioning
confidence: 99%
“…In the past two decades, many theoretical frameworks and methodological approaches on how to measure research impact and returns have been developed (Banzi et al 2011). A common feature of all these models is that they assess impact on many dimensions and try to integrate multidimensional categorisation of benefit (Hanney et al 2007). A set of indicators and metric is generally associated with each category of impact.…”
Section: Challenges In Assessing the Impact Of Researchmentioning
confidence: 99%